Functional Outcome in Patients with Hemorrhagic Stroke - Muhammad Nadeem, Iftikhar Ali Kakar, Shair Zaman Khan, Samiullah Khan, Zafar Mohiuddin, Muhammad Ishfaq (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hemorrhagic stroke is a condition in which the weakened blood vessels ruptures and bleed into surrounding brain parenchyma or in surrounding meningeal spaces. Despite of current advances in determining of its pathophysiology and new treatment approaches, acute hemorrhagic stroke remain a least treatable stroke and the overall mortality ranges from 20 to 40%. Objective: To determine functional outcome in patients with hemorrhagic stroke. Materials and methods: This study was cross sectional descriptive study carried out at the Department of Medicine, Lady Reading Hospital, Peshawar for duration of six months from January 2022 to July 2022. Data collection was done for all the patients by using pre-designed Performa. Data was entered in Excel sheet and analysis of data was done by employing SPSS version 17. Results: Functional outcome according to GCS score among 181 patients was observed as 13(7%) patients had good recovery (return to pre injury functional level), 32(18%) patients had moderate disability (deficit with ability to look after self), 54(30%) patients had severe disability (in able to look after self), 44(24%) patients had persistent vegetative state (no higher mental functions), 38(21%) patients had death (no vital signs). Conclusion: Our study concludes that in our setup 7% patients had good recovery, 18% patients had moderate disability, 30% patients had severe disability, 24% patients had persistent vegetative state while the motility rate was 21% patients. Keywords: functional outcome, hemorrhagic, stroke.